A cloud-based platform for the non-invasive management of coronary artery disease. Issue 8 (13th September 2020) - Sakellarios, Antonis; Correia, Joao; Kyriakidis, Savvas; Georga, Elena; Tachos, Nikolaos; Siogkas, Panagiotis; Sans, Francisco; Stofella, Paolo; Massimiliano, Valiani; Clemente, Alberto; Rocchiccioli, Silvia; Pelosi, Gualtiero; et al.
ABSTRACT: We present the architecture and the usability testing of a novel cloud-based platform, which integrates cyber-physical systems and interoperability standards enabling a clinical decision support system for risk stratification, diagnosis, prognosis and treatment of CAD. In this work multi-disciplinary human data were used for the development of machine learning and computational biomechanics based predictive models. Two Lab-on-Chip devices have been integrated into the cloud platform. A targeted RNA-panel provides the mRNA gene expression values for the stratification algorithm. The results of the usability testing demonstrate that the platform is efficient, accurate and performs all developed tasks quickly.